Alterations induced in the micellization behavior of dioctyl sodium sulfosuccinate in the presence of imidazolium-based surface-active ionic liquids in aqueous medium. Issue 3 (1st March 2023) - Kumar, Harsh; Kaur, Gagandeep; Gupta, Kirti
Abstract: The present work describes the effect of 1-nonyl-3-methylimidazolium bromide [C9 mim][Br] and 1-dodecyl-3-methylimidazolium bromide [C12 mim][Br] on aggregation behavior of anionic surfactant dioctyl sodium sulfosuccinate (NaAOT) in aqueous medium by employing different techniques such as conductivity measurement, UV–Visible spectroscopy and FT-IR spectroscopy. The conductivity data of anionic surfactant in the aqueous solution of surface-active ionic liquids is taken experimentally in the temperature range from 293.15 to 308.15 K with the interval of 5 K at various concentrations that is, (0.04, 0.08, 0.12, and 0.16) wt.% of both the SAILs. The critical micelle concentration (CMC) of NaAOT is detected to alter in the presence of both the SAILs. Temperature dependence of CMC obtained from conductivity measurements is utilized to evaluate various thermodynamic parameters of micellization such as, standard free energy of micellization ( Δ G m 0 ), standard enthalpy of micellization ( Δ H m 0 ), and standard entropy of micellization ( Δ S m 0 ). The UV–Visible spectroscopic study is utilized to confirm CMC values obtained from conductivity measurements, which are found to be in good agreement. FT-IR Spectra are recorded to analyze the structural changes that prevailed in both systems. GRAPHICAL ABSTRACT: UF0001